(CMC-PVP) Films Filled with SnO2 Nanoparticles Synthesized by (Solution-Gel) Method (Journal of the College of Basic Education, 2022)
The aim of this work, to prepare and study the effect of calcination temperature on the structural characterizations of (CMC/PVP) filled-SnO2 nanoparticles films. SnO2 nanoparticles have been successfully synthesized by simple chemical method (sol-gel method), using cheap and non-toxic reactants. The obtained SnO2 powder was calcined at different temperatures (400, 600, 800 °C) which led to form of quasi-spherical SnO2 nanoparticles with different nanoscale sizes. The structural properties were studied by X-ray diffraction (XRD), thermo-gravimetric analysis (TGA), scanning electron microscopy (SEM) and infrared spectroscopy (FTIR). The quasi-spherical tin oxide SnO2 nanoparticles with Rutile-type crystal structure were obtained, with different particle sizes (26.47 nm), (26.27 nm) and (31.8 nm) at 400, 600, 800 °C, respectively. The results showed that the particle size and crystallization degree increased with rising the calcination temperature as a result of crystal growth, while the dislocations density decreases with the rising in temperature. The thermo-gravimetric analysis (TGA) demonstrated that at temperature (800 °C) highly crystalline and pure phase of SnO2 nanoparticle were produced.